اثر نصوص القراءة لميدان فهم المكتوب في تحسين الاداء القرائي لدى متعلمي السنة الاولى متوسط - حباس, حفصة (كلية الأدب العربي والفنون, 2024)
تناولنا في هذه الدّراسة أثر نصوص القراءة لميدان فهم المكتوب في تحسين الأداء القرائي لدى متعلّمي السّنة الأولى متوسط، استدعى هذا البحث إبراز نشاط القراءة باعتبارها أولى المهارات وأهمّها، لما لها تأثير لغوي كبير على خزان المتعلم، إضافة إلى التطرّق إلى ميدان فهم المكتوب، الذي يعتبر بدوره من بين أساسيات التّعليم في المنهاج الجديد. ومن هذا تطرقنا في الفصل الأوّل إلى بيان القراءة وفهم المكتوب، ثم انتقلنا في الفصل الثاني إلى الدراسة التطبيقية لنشاط القراءة لميدان فهم المكتوب لمتعلّمي السّنة الأولى متوسط، وتوصّلنا في ذلك إلى أنّ النّصوص القرائية لميدان فهم المكتوب لها أثر وأهمية بالغة في تحسين الأداء القرائي واللّغوي لمتعلّمي السّنة الأولى متوسّط. In this study, we discussed the impact of reading texts in the field of written comprehension in improving the reading performance of first-year intermediate learners. This research called for highlighting the reading activity as the first and most important skill, because it has a significant linguistic impact on the learner’s reservoir, in addition to addressing the field of written comprehension, which is considered In turn, it is among the basics of education in the new curriculum. From this, we touched in the first chapter on a statement of reading and written comprehension, then we moved in the second chapter to the applied study of the reading activity in the field of written comprehension for first-year intermediate learners, and we concluded that reading texts in the field of written comprehension have a great impact and importance in improving the reading and linguistic performance of year-long learners. The first is average.
Keywords: Texts – Reading – Understanding the written - First year overage – the learner.; النّصوص ـ القراءة ـ فهم المكتوب ـ السّنة الأولى متوسط ـ المتعلّم.